Progressive Geological Modeling and Uncertainty Analysis Using Machine Learning - Hong Li; Bo Wan; Deping Chu; Run Wang; Guoxi Ma; Jinming Fu; Zhuocheng Xiao (ISPRS International Journal of Geo-Information, 2023)
Three-dimensional geological modeling is a process of interpreting geological features from limited sample data and making predictions, which can be converted into a classification task for grid units in the geological space. In sedimentary settings, it is difficult for a single geological classification process to comprehensively express the complex geological spatio-temporal relationships of underground space. In response to this problem, we proposed a progressive geological modeling strategy to reconstruct the subsurface based on a machine learning approach. The modeling work consisted of two-stage classifications. In the first stage, a stratigraphic classifier was built by mapping spatial coordinates into stratigraphic classes, which reflected the geological time information of the geological unit. Then, the obtained stratigraphic class was used as a new feature for the training of the lithologic classifier in the second stage, which allowed the stratigraphic information to be implicitly converted into a new rule condition and enabled us to output the lithologic class with stratigraphic implications. Finally, the joint Shannon entropy of two classifications was calculated to evaluate the uncertainty of the total steps. The experiment built a fine-grained 3D geological model with integrated expression of stratigraphic and lithologic information and validated the effectiveness of the strategy. Moreover, compared with the conventionally trained classifier, the misclassification of the lithologic class between different strata in the progressive classification results has been reduced, with the improvement of the F1-score from 0.75 to 0.78.